Pendampingan Guru SD IT Bina Insani Muslim pada pembelajarn Fiqh Amali - Mia Fitriah Elkarimah; Zainal Arifin Madzkur (Universitas Hamzanwadi, 2022)
The weakness of the learning process is one of the problems in Indonesia's education world today. In the learning process, children are less encouraged to develop thinking skills, and they tend to be directed to memorize information so that students are more theoretically brilliant but weak in the application. Coupled with distance learning also gives unsatisfactory results for students because they only receive material without not being practiced. There is a need for changes in the learning process. The purpose of this community service activity is to provide assistance on practical Fiqh learning to teachers at SD IT Bina Insani Muslim. Although the study of material on Fiqh is practically not too deep, it is hoped that the teacher will be able to provide the whole teaching because Islam gives more attention to daily worship. To achieve this goal, training and mentoring SD IT Bina Insani Muslim teachers is a need of Islamic Fiqh Learning (Practical Fiqh). This service activity was carried out at SD IT Bina Insani Muslim in Jatimulya Tambun Selatan. Service partners are all teachers at SD IT Bina Islam Muslim. This service was held on June 14 and 15, 2021. Located in the hall of SDIT Bina Islam Muslim, attended by 23 teachers who were divided into two sessions. Given that the COVID pandemic has not yet ended, this training and mentoring event is divided into two days. The methods used in this implementation are lectures and demonstrations or direct training. The results of community service activities are increasing the ability and understanding of educators in terms of practical fiqh material and increasing and developing the understanding of educator participants in terms of fiqh problems in everyday life